Flexicurity - issues and challenges (Dublin, 2007)
"This issue of Foundation Findings deals with flexicurity in Europe. Flexicurity is a policy approach that attempts to combine flexibility of labour markets for employers and security of employment for employees. Foundation Findings provide pertinent background information and policy pointers for all actors and interested parties engaged in the current European debate on the future of social policy. The contents are based on Foundation research and reflect its autonomous and tripartite structure."